1769. Viral Suppression Among Participants of the Patient-Centered HIV Care Model Project—A Collaboration Between Community-Based Pharmacists and HIV Clinical Providers. (26th November 2018) - Byrd, Kathy; Hou, John; Clay, Patrick; Bush, Tim; Delpino, Ambrose; Shankle, Michael; Camp, Nasima; Kirkham, Heather; Hazen, Ronald; Weidle, Paul
Abstract: Background: The patient-centered HIV care model was developed to integrate community pharmacists with HIV clinical providers to deliver patient-centered HIV care. The project required 10 clinics to share, with their partnered community-based pharmacists, patients' medical histories, laboratory results, and medications. Pharmacists reviewed the clinic data and worked directly with participants and/or their partnered clinics to make recommendations and discuss potential intervention strategies for identified therapy-related problems. Methods: We calculated the proportion of persons virally suppressed (<200 copies/mL at the last test in each of two 12-month measurement periods), pre- and post-model implementation. Included in the analysis were persons with ≥1 HIV viral load in each measurement period. McNemar's test was used to compare the proportion virally suppressed, pre- and postimplementation. Multivariable logistic regression was used to determine factors associated with viral suppression, postimplementation. Participant demographics and the proportion of days covered (PDC; a measure used to calculate adherence to medication therapy) were used as explanatory variables in the model. The PDC was modified to account for the time to the last viral load in the measurement period, and was stratified into 4 categories: ≥90%, <90–80%, <80–50%, and <50%. Results: With 765 persons enrolled, the plurality of those included in the analysis ( n = 648) were non-Hispanic black ( n = 286), male ( n = 470), and had a median age of 49 years (IQR=38–56). Viral suppression improved 16.3% from 73.9% to 85.9%, pre- to postimplementation ( P < 0.001). Persons who had higher modified PDC (OR 1.9 per category level; 95% CI 1.4–2.6), were currently employed (OR 4.1; 1.6–12.8), or age >50 years (OR 4.7; 2.1–11.8), had greater odds of being suppressed. Non-Hispanic black persons were less likely to be suppressed (OR 0.2; 0.1–0.6); however, viral suppression among this group improved from 62.5% to 77.6%, pre- to postimplementation ( P < 0.001). Conclusion: Collaborations between community pharmacists and HIV clinic providers that seek to identify and address HIV therapy-related problems can lead to improved viral suppression among persons living with HIV. Disclosures: P. Clay, Jaguar Health, Inc.: Consultant and Speaker's Bureau, Consulting fee and Speaker honorarium. Merck & Co., Inc.: Investigator, Research grant. A. Delpino, Walgreens: Employee and Shareholder, Salary.